2022
DOI: 10.3389/fnhum.2022.736688
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in the Elderly: Mechanisms and Perspectives

Abstract: Chronic pain affects a large part of the population causing functional disability, being often associated with coexisting psychological disorders, such as depression and anxiety, besides cognitive deficits, and sleep disturbance. The world elderly population has been growing over the last decades and the negative consequences of chronic pain for these individuals represent a current clinical challenge. The main painful complaints in the elderly are related to neurodegenerative and musculoskeletal conditions, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 160 publications
0
24
1
1
Order By: Relevance
“…A further meta-analysis of aOR and uOR revealed that advanced age was a protective factor for CPSP in patients who underwent VATS. This phenomenon may be related to increased pain thresholds due to aging and decreased pain perception, organ dysfunction, and other conditions that can seriously affect chronic pain perception and response [ 44 ]. Moreover, older people are more stoic regarding pain and more reluctant to report pain when it occurs than younger people are [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further meta-analysis of aOR and uOR revealed that advanced age was a protective factor for CPSP in patients who underwent VATS. This phenomenon may be related to increased pain thresholds due to aging and decreased pain perception, organ dysfunction, and other conditions that can seriously affect chronic pain perception and response [ 44 ]. Moreover, older people are more stoic regarding pain and more reluctant to report pain when it occurs than younger people are [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between age and pain perception remains uncertain. Some studies have reported decreased pain perception in older patients due to the degeneration of neurological systems, while other studies have reported decreases in the pain threshold in older patients, thus increasing pain perception ( 26 ). “Opiophobia,” a term introduced in the 1980s, might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the symptoms experienced by women when they reach menopause, fatigue is one of the most common and is reportedly the one most subjectively distressing[ 48 ]. Physical pain may be part of the picture[ 49 ]. The burnt out feeling, the belief that there’s no further joy to expect in life, nothing to look forward to, constitutes a major emotional burden.…”
Section: Burnout and Menopausementioning
confidence: 99%